THE CONTENT OF NATIONAL INTERESTS IN THE SPHERE OF SECURITY AND DEFENCE OF UKRAINE AND NATO STATES: A COMPARATIVE ANALYSIS - Yurii І. Hrutsenko (Alfred Nobel University Journal of Law)
The article is devoted to a comparative analysis of the content of national interests in the sphere of security and defence of Ukraine and NATO countries in order to determine the vector of further development of security policy in Ukraine. The scientific positions of scientists on the commonality of national interests and their place in the security policy of our country and the Alliance are studied. The key aspects of the strategic concepts of both states are described in chronological order. The author emphasises NATO’s clear position on condemning Russia’s invasion of Ukraine, Russia’s repeated violations of international humanitarian law and support for the establishment of a strong and independent Ukraine as a guarantee of stability in the Euro-Atlantic area. The author analyses the legal basis for bilateral relations between Ukraine and the Alliance: the main provisions of the Charter on a Distinctive Partnership between Ukraine and NATO (1997), the Declaration on Amendments to the Charter on a Distinctive Partnership (2009), and Ukraine’s NATO Strategy (2002). The problem of permanent search for improvement of the mechanisms of ensuring the security policy of Ukraine and NATO in order to counter new threats from the enemy - Russia, and to ensure security in Europe is raised. The national legislation on Ukraine’s political course and security strategies is studied. It is concluded that bilateral relations between Ukraine and NATO to preserve and protect their common interests in the context of security and defence policy are a guarantee of peace in the European region and countering aggressive states in the East (the Russian Federation, the Belarusian Federation). It is emphasised that in the period of globalisation and redistribution of levers of influence in the world, establishing cooperation with other states to preserve and protect common interests is one of the ways to guarantee peace and security. NATO membership is a priority for Ukraine, which is enshrined in both Ukrainian legislation and international treaties.